2014
DOI: 10.2166/wh.2014.093
|View full text |Cite
|
Sign up to set email alerts
|

Cyclospora cayetanensis travels in tap water on Italian trains

Abstract: Tap water samples from the toilets of an Italian national railway train were collected over a period of 10 months and tested for the presence of Cyclospora cayetanensis (C. cayetanensis) using EvaGreen® real-time polymerase chain reaction (RT-PCR) assay coupled with high resolution melting (HRM) analysis for protozoan detection and oocyst quantification. C. cayetanensis positive samples were detected in March, April, and May 2013, with the number of oocysts of 4, 5, and 11 per liter, respectively. This is the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 21 publications
0
11
0
2
Order By: Relevance
“…Cyclospora cayetanensis contaminated water has also been found in developed countries. In Italy, treated wastewater, tap water, and well water was found, by molecular methods, to be contaminated by C. cayetanensis [188]. In Spain, drinking water treatment plants (DWTP), wastewater treatment plants (WWTP) and rivers were tested—oocysts were present in one of the rivers investigated [190].…”
Section: Transmission and Epidemiologymentioning
confidence: 99%
“…Cyclospora cayetanensis contaminated water has also been found in developed countries. In Italy, treated wastewater, tap water, and well water was found, by molecular methods, to be contaminated by C. cayetanensis [188]. In Spain, drinking water treatment plants (DWTP), wastewater treatment plants (WWTP) and rivers were tested—oocysts were present in one of the rivers investigated [190].…”
Section: Transmission and Epidemiologymentioning
confidence: 99%
“…In contrast, with using the same method (PCR/HRM), no genetic variability was found between C. cayetanensis oocysts in samples obtained from edible shellfish collected from Turkey (Izmir) using internal transcribed spacer (ITS)-2 gene primers (Lalonde et al 2013). Furthermore, Giangaspero et al (2015) found that all C. cayetanensis collected from tap water samples from the toilets of an Italian national railway train had the same PCR/ HRM characteristics targeting the ITS-2 gene. Adam et al (2000) identified the intra-genomic variation in ITS-1 genes of C. cayetanensis rRNA isolated from a variety of sources, including raspberry, cases from Guatemala, and pooled and individual isolates from Peru suggesting that these multiple sequences could represent multiple clones from a single clinical source or, more likely, variability of the ITS-1 region within the genome of a single clone.…”
Section: Discussionmentioning
confidence: 94%
“…Regarding chimpanzees from WARC, it is possible that the contamination might have been acquired locally, since the animals were not recently moved or imported from other areas. In Italy, humans have been found to harbour C. cayetanensis [ 34 - 36 ], and this parasite has also been isolated from stored tap water [ 37 ].…”
Section: Resultsmentioning
confidence: 99%